Mean Percentage of Skin and Visible Fat in 10 Chicken Carcass Weight - Fereidoun, Heydarpour; Bahram, Amini; Soltanieh, Kalantari; Sadraddin; Abbass, Akbari; Pouria, Heydarpour (International Journal of Poultry Science, 2006)
Chicken skin is not removed from the whole carcass before cooking in Iran and people prefer chicken with higher weight. The objective of this study was to distinguish the mean percentage of chicken skin and visible fat to chicken carcass weight. The ratio of chicken skin and visible fat to total chicken carcass weight in 10 weight groups were studied. These groups had approximate weight of 1100, 1200, 1300,1400,1500,1600,1700,1800,1900 and 2000 g. Samples were randomly collected 10 times, each time 20 chickens from Kordan slaughterhouse product from each weight were selected. The skin and visible fat were removed from the carcass and weighted. The mean percentage of skin and visible fat ratio to total chicken carcass weight were calculated in these 10 chicken weight groups separately. The mean percentage of poultry skin and visible fat ratio to total chicken carcass weight in these 10 weight groups were 11.7±1.5, 12.3 ±1.8, 12.8 ±1.9, 13.2±1.2, 14.1±1.3, 14.3±1.9, 14.1±1.5, 14.7±2.1, 14.9±1.9, 15.2±2.1 respectively. The minimum percentage was 8% and the maximum was 20% in total samples. Chicken carcass was conditioned in plastic bags without removing the skin and visible fat by the slaughterhouse. Skin and visible fat comprise 8-20% of chicken carcass weight, chicken with higher weight have higher percentage of skin and visible fat. Hence, chicken carcass with lower weight should be purchased and skin and visible fat has to be removed before cooking.